Tourism and Demography - Hsu, Cathy H. C.; Smith, Karen; Watson, Sandra (Oxford, UK : Goodfellow, 2011)
Demography is the most important external factor that will shape the future of the tourism. Current demographic trends will change the demand for tourism and the available workforces, which will fundamentally impact on how the industries are structured, how they operate, and how they develop in a sustainable manner. The tourism industry has to know how, why, when and what will occur, the consequences for the industry, and the strategies that need to be put in place now to combat this change. Tourism and Demography sets out answer these questions through a collection of informed expert opinions about demography trends and how they will shape the future of the tourism industry. Written by a team of international and well respected practitioners and academics, it explores the trends and their implication in a variety of tourism contexts, addressing issues such as: population growth, declining fertility rates, increased longevity, and immigration and labour migration; Generation Y in the context of Travel Futures, Volunteer tourism and global citizenship; International contexts and the need for change strategies; such as Arizona and US Tourism, Asian tourism and Micronesian islands. While demographic change occurs slowly, it shapes workforce structure, levels of disposal income, retirement, and motivational drivers of different cohorts, health, activity, what we consume and more. This book is vital for all students, academics, operators and researchers to further understand of the phenomena of demography and tourism, the changes that will occur and the strategies that need to be adopted.
Keywords: Tourism -- Forecasting; Demography